The structure-sensitivity of memory access: evidence from Mandarin Chinese - Dillon, Brian; Chow, Wing-Yee; Wagers, Matthew; Guo, Taomei; Liu, Fengqin; Phillips, Colin (Frontiers in Psychology, 2014)
The present study examined the processing of the Mandarin Chinese long-distance reflexive ziji to evaluate the role that syntactic structure plays in the memory retrieval operations that support sentence comprehension. Using the multiple-response speed-accuracy tradeoff (MR-SAT) paradigm, we measured the speed with which comprehenders retrieve an antecedent for ziji. Our experimental materials contrasted sentences where ziji’s antecedent was in the local clause with sentences where ziji’s antecedent was in a distant clause. Time course results from MR-SAT suggest that ziji dependencies with syntactically distant antecedents are slower to process than syntactically local dependencies. To aid in interpreting the SAT data, we present a formal model of the antecedent retrieval process, and derive quantitative predictions about the time course of antecedent retrieval. The modeling results support the Local Search hypothesis: during syntactic retrieval, comprehenders initially limit memory search to the local syntactic domain. We argue that Local Search hypothesis has important implications for theories of locality effects in sentence comprehension. In particular, our results suggest that not all locality effects may be reduced to the effects of temporal decay and retrieval interference.